A Novel Fuzzy-Logic Approach for Furan Estimation in Transformer Oil - Abu-Siada, Ahmed; Lai, Sin; Islam, Syed (IEEE Power Engineering Society, 2012)
An ultraviolet-to-visible (UV-Vis) spectroscopic analysis based on the fuzzy-logic approach has been developed for furan content measurement in transformer oil. Following the successful identification and quantification of furan derivatives in transformer oil by the ASTM D 5837 standard, the new approach is able to approximate the furan content with a more convenient and economical method. Since the furan concentration level would determine the absorption intensity in the UV-Vis spectral range, the fuzzy-logic software model developed would exploit this characteristic to aggregate the furans content level in transformer oil. The UV-Vis spectral response sensitivity to ambient temperature was also studied. The proposed technique provide a convenient alternative to conventional techniques, namely: high-performance liquid chromatography (HPLC) or gas chromatography-mass spectrometry (GC/MS) methods.